Association between metformin and physical activity with glucose control in adults with type 2 diabetes. Issue 2 (15th December 2020) - Abdalhk, Diana; Riddell, Michael C.; Swayze, Sarah; Kuk, Jennifer L.
Abstract: Objective: To examine the combined association between metformin use and physical activity on HbA1c in adults with type 2 diabetes. Research Design and Methods: Adults with type 2 diabetes from NHANES continuous survey (1999‐2018, n = 6447) were classified as active and inactive based on self‐reported engagement in moderate‐to‐vigorous or vigorous physical activity (MVPA or VigPA) and metformin use over the last month. Results: There was a significant negative main effect of metformin usage on HbA1c levels, independent of whether individuals engaged in modest levels of MVPA or VigPA. Moreover, there was a higher prevalence of metformin users with a HbA1c < 6.5% than non‐metformin users with no differences by activity status (36.1%‐39.5% versus 24.9%‐29.7%, respectively). There was a significantly lower HbA1c level ( P = .007) and trend for a higher odds of having a HbA1c that achieved the clinical target of <7% (OR, 95% CI = 1.2, 1.0‐1.4, P = .06) in the MVPA than non‐MVPA group for only those not using metformin. For those using metformin, there was no difference in HbA1c levels by either MVPA or VigPA (both P > .05). Conclusions: There appears to be independent benefits of metformin and regular physical activity on glucose control, but the impact of these two treatments are not necessarily additive. Based on this analyses, the benefit of physical activity on HbA1c levels in type 2 diabetes is likely more apparent in those not taking metformin, as compared to those who are. Abstract : There appears to be independent benefits of metformin and regular physical activity on glucose control, but the impact of these two treatments are not necessarily additive. Based on these analyses, the benefit of physical activity on HbA1c levels in type 2 diabetes is likely more apparent in those not taking metformin, as compared to those who are.